Pemenuhan Hak Atas Pendidikan (Dasar) bagi Komunitas Adat Terpencil di Perbatasan antar Negara (Studi Kasus di Provinsi Kalimantan Barat, Nusa Tenggara Timur) - Rully Rachman (Badan Strategi Kebijakan Hukum, 2012)
The Indonesian Government still has limitations in handling areas that are geographically difficult to reach. In such a circumstance, there are several remote areas that are inhabited by Indonesia citizens in the form of indigenous communities who are isolated from other residents in the vicinity.Article 28 C Paragraph (1) of the Constitution of the Republic of Indonesia Year 1945 states that